GE_GERICHTE A/1269/2008 vom 23. September 2002 - GE Cour de justice (2002)
; PC ; PRESTATION COMPLÉMENTAIRE ; PRESTATION D'ASSURANCE INDUE ; RESTITUTION(EN GÉNÉRAL) ; PERCEPTION DE PRESTATION; CAS DE RIGUEUR ; DÉNUEMENT | LPGA25; OPGA4